Assessment of Calamus tenuis fruits extract on blood glucose level elevation and its antibacterial potency - Sarkar, Hema; Sharin, Tasfia; Mamun, Muhammad Shamim Al (Creative Pharma Assent, 2018)
Investigation of anti-hyperglycemic and antibacterial activity of the fruit extract of Calamus tenuis was carried out. Soxhlet extraction was done using petroleum ether, ethyl acetate and methanol. Anti-hyperglycemic activity was done by Oral Glucose Tolerance Test.The results indicated that methanol extract (500 mg/Kg) showed nearly same potency of blood glucose lowering capacity (4.82 ± 0.730 mmol/L) compared to the glibenclamide (standard drug). Antibacterial activity was investigated using disc diffusion method. Antibacterial tests revealed that S. aureus was resistant to all the solvent extracts. Ethyl acetate and methanol extracts showed moderate antibacterial capacity against both Micrococcus and V. cholerea whereas petroleum ether showed nothing. Zone of inhibition of Ethyl acetate and methanol extracts (200 mg/mL dose) for E. coli were very close to positive control (17.00 ± 0.816 and 18.75 ± 1.258 mm respectively; positive control value was 19.00 ± 1.414 and 21.00 ± 1.414 respectively ). In case of methanol zone of inhibitions were greater than other solvent extracts against all tested bacterial species. From the present research it can be recapitulated that due to the biological activity of C. tenuis fruit it may satisfy as a new candidate for the emergence of medicines.